Road Carrying Capacity Assessment of the Heterogeneous Traffic System of Kolkata - Malay Mondal; Nayan Dey; Payel Das (Indonesian Journal of Community Services, 2023)
As an important component of the urban transportation system, the urban road network plays a crucial role in urban spatial structure, urban traffic operations, and socio-economic activities. The significance of capacity analysis and traffic operations helps in identifying the traffic condition and structure in urban areas in Kolkata city. Traffic congestion is a unique situation when the number of vehicles is much greater than the road-carrying capacity. A growing urban area creates complex problems in daily life with traffic. Technologies have continued to impact society over the years, improving our standard of living and quality of life. Advances in telecommunications, the Internet of Things, cloud and edge computing, scalable storage, and data analytics have made fast computing and data-empowered insights. Road carrying capacity has been measured using speed modeling, PCU (Passenger Car Unit) method, and vehicle area occupancy method. Sinthi More, Chiria More, Shyambazer, Park Circus 7 point, Sealdah, Central Avenue, Strand Road, Maniktala, Rajabazer,  Girish Park, Science city more, Panchanna Gram, Tapsia More, Minto Park, P.G.Hospital, Hestings, Golpark, Goriahat more, Kalighat, Taratala auto stand, Behala police station, Behala Chowrasta, Patuli Jheel Park, Goria sitala mandir, Green view, Ruby, Nature park, Garden reach police station, Metiabruz, Chowbaga, Ajay Nagar junction points (31survey point) have been taken for this survey. About Thirteen roads have been taken in Kolkata city to do this project. The average vehicle velocity is 19.2 km/h in Kolkata city.